Re-ordering Our Priorities - Serrette, Owen (Pan Trinbago Supplement)
Owen Serrette, President of Pan Trinbago, addressed the launching of Pan Trinbago Capital Investment Programme at the Central Bank Auditorium on May 29. Serrette congratulates the Government's initiative to make $7.5 million available to the Steelband Movement which is to be expended on a steelband concert hall, pan cottages and promotional material and states Pan Trinbago's comprehensive series of action plans.
Keywords: Steel bands (Music) -- Administration -- Trinidad and Tobago; Steel band music -- Trinidad and Tobago; Pan Trinbago (Organization); Capital investments -- Trinidad and Tobago